To know or to believe, that is not the question. Opinion and knowledge in Plato’s Protagoras (Circe de clásicos y modernos, 2018)
The human will as it is analyzed in the Protagoras deals with the epistemic state of the agent in the moment of making a decision. We will try to show that, according to Socrates, it makes no difference if the agent either knows that something is good or thinks something is good (at least for himself): as long as it is pondered that way, the agent will choose it. Man’s will is, then, an inevitable prey of his epistemic state, whether it is constituted of knowledge or of opinions.
Keywords: incontinence; will; epistemic state; theory of action; ethics